Kegiatan Meronce Mengoptimalkan Perkembangan Otak Kecil pada Anak Usia Dini - Syafitri, Destriana; Aprisa, Hesti; Junita, Yepi (TSAQOFAH, 2024)
Early childhood is children aged 0-6 years. At this age children experience rapid and short development. Optimal motor development at an early age can support later life, by providing stimulation to children, one of which is meronce activities. The cerebellum, which is located at the bottom of the brain or the cerebellum, functions to regulate fine motor control, balance and coordination. The activity of making bracelets from beads can stimulate children's fine motor skills. In this case the research uses experimental methods. Using a sample of three children, aged four years, five years and six years. Collection of experimental data and documentation.. The aim of this research is to find out how optimal meronce activities are in the development of the cerebellum in early childhood. Based on observations in the field, young children are still categorized as having not developed their fine motor skills as they should. So it is important for adults, parents and teachers to provide stimulation to children from an early age one of them is ronce activity.